Peruvian traditions anthologated - Kapsoli Escudero, Wilfredo (2019)
Reviewing the anthologies of the Traditions of Ricardo Palma, we have found to date about 22 books with their respective authors. The selection criteria are related to the decision of each anthologist. Thus, we have Traditions together with an order in accordance with the stages of National History: Incas, Conquest,Colony, Independence, and Republic. Others based on thematic criteria: Indians, Spaniards, Creoles, and Mestizos; followed by his professions as tailors, notaries, hairdressers, aguateros, camaroneras, bakers and silversmiths. As an example, we present Ricardo Palma himself and his daughter Angelica as the first compilers. The first with his book “El Demonio de Los Andes” and the second with “El Palmade la Juventud”.